Never mind Brexit, it's time to celebrate 'TRexit'. Issue 3 (28th May 2019) - Simson, Nick; Rusere, Jonah; Stroman, Luke; Popert, Rick
Abstract : In this comment piece the authors discuss the 'Trexit' initiative to encourage the complete cessation of transrectal prostate biopsies in favour of the transperineal route.